Understanding the interplay between cathode catalyst layer porosity and thickness on transport limitations en route to high-performance PEMFCs. (21st June 2019) - Sassin, M.B.; Garsany, Y.; Atkinson, R.W.; Hjelm, R.M.E.; Swider-Lyons, K.E.
Abstract: We examine the interplay between cathode catalyst layer (CL) porosity/thickness on mass transport limitations in single cell fuel cells comprised of Pt/C-based CLs fabricated via ultrasonic spray deposition onto polymer electrolyte membranes. We determine that the pore size distribution remains unchanged as CL thickness increases from 3.8 to 11.8 μm, but porosity decreases with increasing CL thickness. The decrease in porosity results in an increase in mass transport resistance for thicker CLs, but does not result in an increase in charge transfer resistance for the oxygen reduction reaction. We found that a fuel cell comprising a 7.5 μm-thick cathode CL delivers the highest performance (1 A cm −2 at 0.60 V at 80 °C in H2 |Air at a relative humidity of 50% under ambient pressure). We attribute this high performance to the CL striking an optimal balance between solid and void networks, with the solid networks facilitating transport of H + /e − to the Pt electrocatalyst, and the void network ensuring adequate transport of O2 to, and H2 O away from, the Pt electrocatalyst. Highlights: Pore size distribution is constant for 3.8 to 11.8 μm-thick catalyst layers. Porosity decreases as catalyst layer thickness increases. Minimal change in charge transport resistance as catalyst layer thickness increases. Mass transport resistance increases with catalyst layer thickness. Optimal PEMFC performance obtained for a 7.5 μm-thick catalyst layer.